PENGARUH MODEL SELF ORGANIZIED LEARNING ENVIRONMENT BERBANTUAN GOOGLE SITES TERHADAP LITERASI SAINS DAN SELF REGULATION KELAS XI PADA MATA PELAJARAN BIOLOGI - Kesumawardani, Aryani Dwi; Huda, Nur; Sari, Aulia Novita; Oktafiani, Raicha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Quality education plays a crucial role in shaping students to become critical thinkers, independent learners, and scientifically literate individuals. However, suboptimal instructional models continue to hinder the development of students’ science literacy and self-regulation skills. This study aims to investigate the effect of the SelfOrganized Learning Environment (SOLE) model assisted by Google Sites on students' science literacy and self-regulation abilities. A quantitative approach with a quasi-experimental design was employed, and samples were selected purposively from Grade XI students. Data were collected through post-tests and questionnaires administered at the end of the learning process. The results show that the implementation of the SOLE model facilitated active student engagement, encouraged independent learning management, and promoted effective use of digital learning resources. Students responded positively to the learning process, demonstrating high enthusiasm and increased autonomy in organizing their learning. These findings suggest that the SOLE model assisted by Google Sites has a positive impact on enhancing students’ science literacy and self-regulation. This model offers a promising alternative learning strategy aligned with the demands of 21st-century education.